2011
DOI: 10.1007/s10464-011-9457-7
|View full text |Cite
|
Sign up to set email alerts
|

Small Wins Matter in Advocacy Movements: Giving Voice to Patients

Abstract: In this article, the various players are delineated in a story of a contested illness and patient advocacy, played out within the corridors of federal power. It is suggested that the mistreatment and negative attitudes that health care providers and others have towards those with chronic fatigue syndrome (CFS) is possibly due to the social construction of this illness as being a "Yuppie flu" disease. Institutional factors are identified that created these norms and attributions, as well as the multiple stakeho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…A First Person Account usually consists of an integrative Introduction and Discussion that bookends narratives from collaborating authors, thus providing a "360" window into the diverse and situated perspectives of various stakeholders engaged in community research and action. A few examples are: Brown et al (2013), Case et al (2014), Jason (2012) and Smith et al (2014).…”
Section: Types Of Articlesmentioning
confidence: 99%
“…A First Person Account usually consists of an integrative Introduction and Discussion that bookends narratives from collaborating authors, thus providing a "360" window into the diverse and situated perspectives of various stakeholders engaged in community research and action. A few examples are: Brown et al (2013), Case et al (2014), Jason (2012) and Smith et al (2014).…”
Section: Types Of Articlesmentioning
confidence: 99%
“…Jason (2012) suggested that the erroneous inclusion of people with primary psychiatric conditions in CFS samples would have detrimental consequences for the interpretation of epidemiologic, etiologic and treatment efficacy findings. In this dynamic process, one research finding would often influence another in often unexpected ways.…”
Section: Stigma Regarding Chronic Health Conditionsmentioning
confidence: 99%
“…Efforts to study ecological exchanges between individuals and their social environments have been limited in number and scope (Jason & Glenwick, 2012). When the effect of environment on behavior has been studied, it has rarely been extended to the effects of behavior on environment broadly (e.g., Todd, Allen, & Javdani, 2012).…”
mentioning
confidence: 99%
“…Yet reaching a widely accepted operationalization of this condition has been difficult to achieve (Brown, Jason, Evans, & Flores, 2013). Research has delineated a number of obstacles that have contributed to the slowing of such progress and resistance from some professionals in the healthcare community (Jason, 2012). This article seeks to illustrate the need for applying flexible, robust mixed-method strategies when investigating the nature of the illness and the experiences of the patient community.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable patient and scientific activity in the ME and CFS field has focused on three areas: establishing estimates of the prevalence for the illness, addressing negative stigma towards patients due to the name of the illness, and the creation and evaluation of treatment strategies (Jason, 2012). This article will examine where research in these domains has faced limitations based on study design, and will reflect on the effects of methodological choices on the understanding of ME and CFS.…”
Section: Introductionmentioning
confidence: 99%